2013
DOI: 10.1111/vde.12075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hair loss in cats occurring after treatment with a topical flea control product

Abstract: Microscopic changes in the hair follicles of affected cats were consistent with self-induced trauma or barbering behaviour. All changes were reversible and paralleled findings associated with well-established, topical flea control products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although that 39.6% w/v formulation of spinetoram was non-irritant, some field reports were received of focal hair loss from the application site in a small percentage of treated cats. This problem was attributed to the high viscosity of the formulation and so a formulation with a lower concentration and viscosity was developed [ 6 ]. Preliminary laboratory effectiveness studies were completed, and tolerability studies in client-owned cats demonstrated the acceptability and safety of an 11.2% formulation (unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
“…Although that 39.6% w/v formulation of spinetoram was non-irritant, some field reports were received of focal hair loss from the application site in a small percentage of treated cats. This problem was attributed to the high viscosity of the formulation and so a formulation with a lower concentration and viscosity was developed [ 6 ]. Preliminary laboratory effectiveness studies were completed, and tolerability studies in client-owned cats demonstrated the acceptability and safety of an 11.2% formulation (unpublished observations).…”
Section: Introductionmentioning
confidence: 99%